Representasi Guru dalam Pemberitaan Kasus Kekerasan Seksual di Media Kompas dan Tempo: Analisis Wacana Kritis - Usman; Arlin; Mahmudah (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to examine the representation of teachers in the coverage of sexual violence cases in Kompas and Tempo media. The approach used is Critical Discourse Analysis Social Actor Approach from Theo van Leeuwen. Data and data sources are words, phrases, sentences, and paragraphs in sexual violence news related to teachers and other social actors in Kompas and Tempo media. Data collection techniques are identification, classification, and analysis. The results of this study indicate that there is a form of exclusion found in the news in Kompas media in the form of passivation that eliminates certain social actors so as to direct readers to focus on the teacher's social actors. The form of inclusion found in Kompas media is in the form of differentiation, association, categorization, identification, and association which aims to show partiality to victims, and clarify the identity of the perpetrator, and represent sexual violence as a system problem, not a single problem. The forms of inclusion found in Tempo media are abstraction, determination and categorization which show partiality to victims as well as a form of media criticism of teachers and the government in order to create a safe educational environment.